Permanência de alunos nos cursos presenciais e a distância em Administração: contribuições para a gestão acadêmica - Silva, João Augusto Ramos e (2012)
Distance education has been gaining attention in recent years due to the capacity of expansion of under graduation education and also to including a group of people who otherwise could not hold a degree. The objective of this research was to identify variables that influence the process of permanence of Administration Business students, comparing results of distance education to presential education, and taking the State University of Maranhão (Uema) as a case to be studied. As the main theoretical framework of this study, we chose the Student Integration Model of Tinto (1975), considered the first academically recognized proposal for determining the variables that interfere in the process of evasion and retention of students in an undergraduate course. One component of the model captured the interest of comparing the two modalities (presential and distance one) in a special way: social integration, as a result from interactions among students and professors, who are generally poorly explored in empirical studies. The method defined for the study was descriptive with a qualitative basis. The submission of all the variables observed in the literature to an analysis of judges resulted in the definition of three main dimensions and 60 components, namely: (1) Profile of the student, (2) Being in network; and Conditions for permanence. These variables formed the framework for analysis of categorical content, resulting from the application of multiple data collection instruments (two questionnaires and an in-depth interview) that were used in triangulation with secondary data obtained in the actual Enade (2009). As a theoretical contribution of this thesis, it is noted three possibility of integration of three philosophical views: Cognitivism, Constructivism and Connectivism that are interrelated in the management of academic degree courses by the uniqueness of education envisioned by the blended learning as the future trend for higher education. Other contributions are presented in relation to components: individual attributes, work and training, family background, schooling, previous use of ICTs, professors and students interaction, personal commitment and institutional and academic integration.